Pengaruh Model Pembelajaran Index Card Match Terhadap Keaktifan Belajar PAK Siswa Kelas IX SMP N 3 Lintongnihuta, Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Riani Silalahi (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The aim of this research is to determine the positive and significant influence of the index card match learning model on the active learning of PAK students in class IX of SMP N 3 Lintongnihuta, Humbang Hasundutan Regency for the 2023/2024 academic year. The method used in this research is a descriptive quantitative research method. The population is all 191 class IX students of SMP Negeri 3 Lintongnihuta for the 2023/2024 academic year who are Protestant Christians and a sample of 48 people was determined using random sampling techniques. Data was collected using a positive closed questionnaire with 32 items, namely 16 items for variable Lintongnihuta, Humbang Hasundutan Regency 2023/2024 Academic Year: 1) Test the analysis requirements: a) positive relationship test obtained a value of rxy = 0.607 > rtable(a=0.05,n=48) = 0.284. b) Testing a significant relationship obtained a value of t = 5.179 > t table (a = 0.05, dk = n-2 = 46) = 2.021. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂="17.02"+0.65X. b) Regression coefficient of determination test (r2) = 36.8%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=20, dk denominator=n-2=48-2=46) namely 26.77 > 1.51. Thus Ha is accepted and H0 is rejected.